Missiological Implications of Christianizing the Social Order with Special Reference to the United Church of Canada - Jay, C. Douglas (Toronto journal of theology, 1996)
The central questions addressed in this article are: (1) What are the missiological implications of the concept of Christianizing the social order, especially in the United Church of Canada and its founding churches? and (2) Has the concept any continuing validity in our increasingly pluralistic society? My particular interest in these questions relates to my role as secretary of the Commission on World Mission, which reviewed mission policy and practice of the United Church of Canada and its founding churches up to 1966, and. which, by the adoption of its recommendations in that year by the General Council, became the official mission policy statement of the church. Reference will also be made to other official reports, especially the 1934 report on Christianizing the social order.